RIVALS FOR POWER? - Briggs, George (My University, 1965)
: This is a study of Edward Blake and Alexander Mackenzie, the two most important men in the Liberal Party of Canada in the immediate post-Confederation period. The difficulties faced by its leader, Alexander Mackenzie, are studied, and particular examination is made of Edward Blake’s reluctance to serve as a loyal cabinet minister and subordinate of Mackenzie. The general conclusion is that Edward Blake’s latent desire to attain the party leadership was activated, fro 1 time to time, by friends and/or ’intriguers', thus accounting for the rather enigmatic behavior of Blake as he pursued the position held by Mackenzie.